PENINGKATAN KECERDASAN NATURALIS MELALUI METODE KUNJUNGAN LAPANGAN (FIELD TRIP) - JUNIARTI, YENTI (Jurnal Pendidikan Usia Dini, 2015)
Abstract: This study was to obtain a picture of the naturalist intelligence activity in children in group B Integrated early childhood Bintuhan and determine the extent of the resulting increase in intelligence naturalist child through the method of field visits. Classroom action research (PTK) by using a research model Kemmis and Mc. Taggart. Held for 2 cycles and each cycle consisted of 7 sessions, consisting of stages: planning, action, observation and reflection. The subjects were children in group B were 10 children, 5 boys and 5 girls. Quantitative data analysis with descriptive statistics that compare the results obtained from the first cycle and the second cycle. While the analysis of qualitative data by analyzing data from the field notes and interviews during the study to the steps of data reduction, data display and data verification. The results showed an increase naturalist method field trips, pre-cycle of 40.4%, an increase on the first cycle of 18:04% to 58.44% and the second cycle increased by 23:06% to 81.5%. Keywords: Field Trip Method, Natural Intelligence, Early Chilhood